Marking of English verbs for past tense: a study of Afghan learners' production - Bahrami, Yar Mohammad (Kansas State University, 2009)
The formation of English past tense by EFL (or ESL) learners has been the object of much second language acquisition research. This study investigates the production and marking of English past tense verbs by 55 adult Afghan EFL learners who use Pashto or Dari as their first language. The participants were first required to produce the past tense while responding to a questionnaire about their daily activities, and then completed a correction task in which sentences with verb errors appeared. The collected data was analyzed based on verb regularity (Pinker & Ullman 2002, Jaeger et al. 1996, Hoeffner 2000, Housen 2000) and the sequential inflection of events or non-events based on inherent lexical aspect (Vendler 1967, Salaberry 2000, Bardovi-Harlig & Reynolds1995, Tickoo 2001, 2005). Results show that the participants were more accurate in marking and producing regular verbs than irregular verbs for the past tense in both experimental tasks. When examining the role of regularity of the verb in the sequential marking of lexical aspect, it was discovered that past tense production of irregular verbs was influenced by the lexical aspectual verb type as non-events exhibited lower accuracy rates for past tense inflection.
Keywords: Marking of Past Tense; Education, Language and Literature (0279)